(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
Fruit development and ripening genes have a close relationship with the regulatory elements that control the development of floral organs. Furthermore, like with many other aspects of plant development, understanding the processes that drive fruit development and ripening necessitates disclosing both the genetic and epigenetic architecture that underpins gene structure and expression. Moreover, there is increasing evidence that epigenetic regulators are important in fruit development and ripening, and that they may work together with hormones and transcription factors. To determine particular chromatin states, epigenetic changes like-as DNA methylation, histone post-translational modifications, and noncoding RNAs can interact with one another. Developments in the plant’s molecular biology have enabled researchers to surpass the limits of classical methodology of study for other crops especially the tomato’s ancestor. In this review, we cover a variety of subjects, including the history of the tomato, the evolution of fruit ripening regulation, and the mechanisms relating to epigenetic regulation in tomato fruit ripening. These findings, according to researchers, may have a significant impact on crop development strategies in fruit-bearing species.